(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
Individuals who attempt conception with donor sperm or donor eggs face many obstacles. They frequently experience social stigma associated with infertility and thus they do not disclose their children about the existence of a donor. When donor-conceived children are made aware of gamete donation, sometimes they claim the right to know their genetic origins. This right is not granted in many States, since the principle of anonymity is laid down in national and international laws. It is therefore appropriate to question the role of genetics in defining parental relations and personal identity. Nonetheless, it is necessary to highlight the detachment between States and candidate health care recipients, who increasingly move from one jurisdiction, where treatment is unavailable for them, to another jurisdiction in order to obtain the treatment they need. In this scenario, the right to know genetic origins has to be discussed.